Answer:
plot the numbers
Step-by-step explanation:
Answer:
6x−7
Step-by-step explanation:
2x−7+4x
=2x+−7+4x
Combine Like Terms:
=2x+−7+4x
=(2x+4x)+(−7)
=6x+−7
7*24 = 168 quarts of water per day goes into barrel.
25*48 = 1200 quarts of waste water picked up
1200÷168 =7.142857143
Answer:
The answer is
![y = 3](https://tex.z-dn.net/?f=y%20%3D%203)
![y = - 4](https://tex.z-dn.net/?f=y%20%3D%20%20-%204)
Step-by-step explanation:
We must find a solution where
![\frac{6}{y + 1} + \frac{y}{y - 2} = \frac{6}{y + 1} \times \frac{y}{y - 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7By%20%2B%201%7D%20%20%2B%20%20%5Cfrac%7By%7D%7By%20-%202%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7By%20%2B%201%7D%20%20%5Ctimes%20%20%5Cfrac%7By%7D%7By%20-%202%7D%20)
Consider the Left Side:
First, to add fraction multiply each fraction on the left by it corresponding denomiator and we should get
![\frac{6}{y + 1} \times \frac{y - 2}{y - 2} + \frac{y}{y - 2} \times \frac{y + 1}{y + 1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6%7D%7By%20%2B%201%7D%20%20%5Ctimes%20%20%5Cfrac%7By%20-%202%7D%7By%20-%202%7D%20%20%2B%20%20%5Cfrac%7By%7D%7By%20-%202%7D%20%20%5Ctimes%20%20%5Cfrac%7By%20%2B%201%7D%7By%20%2B%201%7D%20)
Which equals
![\frac{6y - 12}{(y -2) (y + 1)} + \frac{ {y}^{2} + y }{(y - 2)(y + 1)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6y%20-%2012%7D%7B%28y%20-2%29%20%28y%20%2B%201%29%7D%20%20%2B%20%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%2B%20y%20%7D%7B%28y%20-%202%29%28y%20%2B%201%29%7D%20)
Add the fractions
![\frac{y {}^{2} + 7y - 12 }{(y - 2)(y + 1)} = \frac{6}{y + 1} \times \frac{y}{y - 2}](https://tex.z-dn.net/?f=%20%5Cfrac%7By%20%7B%7D%5E%7B2%7D%20%2B%207y%20-%2012%20%7D%7B%28y%20-%202%29%28y%20%2B%201%29%7D%20%20%3D%20%20%5Cfrac%7B6%7D%7By%20%2B%201%7D%20%20%5Ctimes%20%20%5Cfrac%7By%7D%7By%20-%202%7D%20)
Simplify the right side by multiplying the fraction
![\frac{6y}{(y + 1)(y + 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6y%7D%7B%28y%20%20%2B%201%29%28y%20%2B%202%29%7D%20)
Set both fractions equal to each other
![\frac{6y}{(y + 1)(y - 2)} = \frac{ {y}^{2} + 7y - 12}{(y + 1)(y - 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B6y%7D%7B%28y%20%2B%201%29%28y%20-%202%29%7D%20%20%3D%20%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%2B%207y%20-%2012%7D%7B%28y%20%2B%201%29%28y%20-%202%29%7D%20)
Since the denomiator are equal, we must set the numerator equal to each other
![6y = {y}^{2} + 7y - 12](https://tex.z-dn.net/?f=6y%20%3D%20%20%7By%7D%5E%7B2%7D%20%20%2B%207y%20-%2012)
![= {y}^{2} + y - 12](https://tex.z-dn.net/?f=%20%3D%20%20%7By%7D%5E%7B2%7D%20%20%2B%20y%20-%2012)
![(y + 4)(y - 3)](https://tex.z-dn.net/?f=%28y%20%20%2B%204%29%28y%20-%203%29)
![y = - 4](https://tex.z-dn.net/?f=y%20%3D%20%20-%204)
![y = 3](https://tex.z-dn.net/?f=y%20%3D%203)
32 = 2^5 <==== my answer is too short..lol